1989
DOI: 10.1037/0735-7044.103.6.1356
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of environmentally contaminated Lake Ontario salmon by laboratory rats increases avoidance of unpredictable aversive nonreward and mild electric shock.

Abstract: To determine what behavioral changes are caused by consumption of Lake Ontario salmon, a 30% diet of Lake Ontario or control Pacific Ocean salmon was fed to rats for 20 days. In Experiments 1 and 2 (preference-for-predictability E-maze test), rats fed Lake Ontario salmon developed a preference for predictable food rewards more quickly than did the control rats. In Experiments 3 (passive avoidance) and 4 (conditioned suppression), rats fed Lake Ontario salmon suppressed responding to food far more after the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Immediately after the CPT, each child was asked to report how he or she felt about performing the task. This was in response to Daly's findings (Daly 1992;Daly et al 1989) that rats fed Lake Ontario fish were more reactive to negative events. The child was verbally asked the question "How much fun did you have doing this activity?"…”
Section: Methodsmentioning
confidence: 75%
“…Immediately after the CPT, each child was asked to report how he or she felt about performing the task. This was in response to Daly's findings (Daly 1992;Daly et al 1989) that rats fed Lake Ontario fish were more reactive to negative events. The child was verbally asked the question "How much fun did you have doing this activity?"…”
Section: Methodsmentioning
confidence: 75%
“…Although this procedure cannot rule out chemicals devoid of hormonal activity that may disrupt development through other mechanisms, it can at least rule out compounds like DDT, chlordecone, alkylphenols, and some PCBs, which are estrogen agonists. It is also essential to continue to examine transgenerational effects in animal studies because some pollutants require metabolism in vivo to exert hormonal effects and because neurobehavioral and other developmental effects cannot be addressed with in vitro models (96,97 …”
Section: Discussionmentioning
confidence: 99%
“…A number of early studies with PCB mixtures demonstrated neurobehavioral effects in rodents (23)(24)(25). In more recent studies with single congeners, Schantz et al (6) investigated effects of gestational exposure on days 10-66 of rats to PCB 28 (2,4,4´-triCB; 8 or 32 mg/kg/day), 118 (2,3´,4,4´,5-pentaCB; 4 or 16 mg/kg/day), and 153 (16 or 64 mg/kg/day) on adult rat behavior.…”
Section: Discussionmentioning
confidence: 99%